Soiling type classification and prediction of power loss of a PV panel using CNN - Ahmed, Alvi; Nur, Tahseen Md; Zahid, Omar Tanzim; Ali, Elma Minaz (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.